ANALISIS PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION - Abdillah, Bara Muttaqien (Jurnal Kewirausahaan dan Inovasi, 2023)
This explanatory quantitative research aims to assess and explain whether job satisfaction and job stress have any partial effects on the turnover intention of employees of PT Hashmicro Solusi Indonesia. The independent variables of this research are job satisfaction and job stress, while the dependent variable is turnover intention. From the population of 250 employees from all divisions, 152 people were selected as the respondents, from whom primary data was acquired. The results of the descriptive analysis and multiple linear regression in SPSS version 21 indicate that job satisfaction has a negative and significant effect on the turnover intention and that job stress has a positive and significant influence on the turnover intention. This means that the employees’ turnover intention level is influenced by their job satisfaction and their job stress.